Environmental health effects associated with recycling of sewage for potable purposes: a literature review - Baig, Mirza Jawad G.; Ahmed, Aisha; Aujla, Gurpreet Singh (International Journal Of Community Medicine And Public Health, 2019)
This literature review has been drafted to explore and emphasise the potential environmental health risks and benefits of recycling wastewater especially in areas affected by prolonged drought. With limited water resources, recycled treated sewage water can be used to augment the fresh water supply. This review will provide an understanding of the importance of water recycling and the environmental impacts recycling can have on the environment. A comparison is also provided to understand the environmental effects of untreated sewage on the environment and the potential benefits associated with the recycling. Public health aspect is also elaborated to highlight whether recycled treated sewage is a viable option to be considered for the use as potable water. Literature suggests that recycled treated water has a purifying effect on the environment and can be used for potable and non-potable purposes.